THE BRICS COMMITMENT IN THE PROMOTION OF EQUALITY BETWEEN WOMEN AND MEN: ANALYSIS FROM THE HUMAN RIGHTS AND PEACE PERSPECTIVE - C. G. Fernandez; D. F. Puyana (BRICS Law Journal, 2016)
The contribution of women to peace has been very relevant throughout history. The full and complete development of a country, the welfare of the world and the cause of peace require the maximum participation of women on equal terms with men in all fields. Gender equality has always been seen as an endless project, which should be realized by everyone around the world. The long-term effects of conflict and militarization create a culture of violence that renders women especially vulnerable in a post-war scenario. The interest in involving women and girls in the peace processes often stems from their experiences of armed conflicts, whether primarily as victims or as armed participants. They are aware of the potentials for transformation and reform in periods of peacemaking. Since 2008, the Human Rights Council has been working on the ‘Promotion of the right of peoples to peace.’ Pursuant to resolutions 20/15 and 23/16, the Council decided firstly to establish, and secondly to extend the mandate of the open-ended working group (OEWG) aimed atprogressively negotiating a draft United Nations declaration on the right to peace. The OEGW welcomed, in its second session (July 2014), the approach of the Chairperson-Rapporteur, which is essentially based on the promotion of equality between men and women, and the relationship between the right to life and human rights, peace and development.